Autonomous agents and multiagent systems : AAMAS 2017 Workshops, Visionary Papers, São Paulo, Brazil, May 8-12, 2017, Revised selected papers /: AAMAS 2017 Workshops, Visionary Papers, São Paulo, Brazil, May 8-12, 2017, Revised selected papers. (2017) - Unknown
No abstract available